Brief Report: Associations Between Self-Reported Substance Use Behaviors and PrEP Acceptance and Adherence Among Black MSM in the HPTN 073 Study. (1st September 2020) - Okafor, Chukwuemeka N.; Hucks-Ortiz, Christopher; Hightow-Weidman, Lisa B.; Magnus, Manya; Emel, Lynda; Beauchamp, Geetha; Kuo, Irene; Hendrix, Craig; Mayer, Kenneth H.; Shoptaw, Steven J.
Abstract : Background: Pre-exposure prophylaxis (PrEP) is efficacious for HIV prevention. Black men who have sex with men (MSM) accounted for the largest proportion of new HIV diagnoses in the United States relative to other racial/ethnic groups. Black MSM who use substances are at an increased risk for HIV infection and are ideal candidates for PrEP, but barriers to maintaining PrEP adherence remain a concern. We assessed whether substance use behaviors are associated with initiation and adherence to PrEP among a sample of black MSM in the United States. Methods: Data for this analysis come from the HIV Prevention Trails Network Study 073 (HPTN 073). Substance use behaviors—including alcohol, marijuana, poppers (ie, alkyl nitrites), and stimulants (ie, methamphetamine/cocaine use) including use of these substances before/during condomless anal intercourse (CAI)—were assessed longitudinally through self-report. PrEP adherence was assessed by pharmacological testing in blood. Generalized estimating equations were used to evaluate association between substance use behaviors and PrEP initiation and adherence. Results: Among 226 HIV-negative black MSM, the majority (60%) were 25+ years of age. Most of the substance use behaviors were not significantly associated with PrEP initiation or adherence. However, stimulant use before/during CAI was significantly associated with lower odds of PrEP adherence (adjusted odds ratio = 0.21, 95% confidence interval = 0.07 to 0.61; P = <0.01). Conclusions: These findings suggest that PrEP adherence is feasible among black MSM who use substances. However, black MSM who engage in stimulant use before/during CAI may present a unique group for additional study and support with enhanced behavioral health and support services. Abstract : Supplemental Digital Content is Available in the Text.